Empowering Communities to Improve Behavior Towards Acceptance of Covid-19 Vaccination - Manalu, Sarah Patumona; Nurfahasdi, Meutia (Talenta Publisher, 2023)
Covid-19 has spread throughout the country, and resulted in a pandemic. This virus infects the respiratory system. The affected Indonesian people have more than 4 million people. The incidence rate in Medan City has reached 47,000 cases. Prevention efforts to strengthen the immune system is the Covid-19 vaccination. Even though the vaccine is declared safe, there are still people who don't want to be vaccinated. Rejection also comes from a group of educated people. This hinders the success of the National Covid-19 Vaccination Program. Vaccination efforts can be successful if carried out simultaneously, so as to form herd immunity. Community empowerment carried out by providing education about Covid-19; the benefits of vaccination; and about herd immunity. They are also invited to vaccinate. People want to vaccinate because they have confidence and understand the information provided. This activity increases the number of vaccination implementations in partner work areas. Until now, the total number of vaccinations has reached 30,500. The plan for the next stage is monitoring community participation in the implementation of vaccinations, as well as conveying information on the benefits of Covid-19 vaccination through videos and online media.